Narrativas de trabalhadoras domésticas estudantes da EJA e suas relações com o saber - Canto, Liana Pereira Machado (Universidade do Vale do Rio do Sinos, 2009)
The present research addresses the relationship women working as house keepers establish with knowledge. The main goal was to understand the relations those women create with school knowledge and the knowledge acquired in their line of work contributing to discussions on the PROEJA. Inspired by Josso’s life history methodology (2004), we interviewed six house keepers who attend night school in a Brazilian project called EJA (Youth and Adult Education), first individually and then collectively. We would like to emphasize the fact that the methodology has led to an opportunity of formation for the six women involved, which Josso calls “formative experience”. The theoretical references are the studies by Schwartz (2000, 2003), Charlot (2000, 2001) and Malglaive (1995) on knowledge and the relations with knowledge; Josso (2004) on formative-research and life history, which has also been the basis for the methodology used on this research; Lagarde (2005) on reflections on gender. The research showed that in the co
Keywords: educação de jovens e adultos; histórias de vida; trabalho doméstico; trabalho-educação; saberes; house keeping; life histories; work-education; youth and adult education; knowledge; Ciências Humanas